Alpha-crystallin can function as a molecular chaperone. - Horwitz, J (1992)
The alpha-crystallins (alpha A and alpha B) are major lens structural proteins of the vertebrate eye that are related to the small heat shock protein family. In addition, crystallins (especially alpha B) are found in many cells and organs outside the lens, and alpha B is overexpressed in several neurological disorders and in cell lines under stress conditions. Here I show that alpha-crystallin can function as a molecular chaperone. Stoichiometric amounts of alpha A and alpha B suppress thermally induced aggregation of various enzymes. In particular, alpha-crystallin is very efficient in suppressing the thermally induced aggregation of beta- and gamma-crystallins, the two other major mammalian structural lens proteins. alpha-Crystallin was also effective in preventing aggregation and in refolding guanidine hydrochloride-denatured gamma-crystallin, as judged by circular dichroism spectroscopy. My results thus indicate that alpha-crystallin refracts light and protects proteins from aggregation in the transparent eye lens and that in nonlens cells alpha-crystallin may have other functions in addition to its capacity to suppress aggregation of proteins.